Predicting Postcesarean Pain: A Prospective Cohort Study Using a 3-Question Questionnaire, Local Anesthesia Infiltration, and Observer Rating - Unyime S. Ituk; Sapna Ravindranath (Pain Research and Management)
Implications: This study highlights the potential of a combined preoperative pain rating questionnaire and anesthesiologist’s predictions to improve postcesarean pain management. By accounting for 27% of the variance in mean postcesarean pain with movement, this approach could enhance pain management outcomes for CD patients.